Beliefs and social behavior in a multi-period ultimatum game - Azar, Ofer H.; Lahav, Yaron; Voslinsky, Alisa (Frontiers in Behavioral Neuroscience, 2015)
We conduct a multi-period ultimatum game in which we elicit players’ beliefs. Responders do not predict accurately the amount that will be offered to them, and do not get better in their predictions over time. At the individual level we see some effect of the mistake in expectations in the previous period on the responder’s expectation about the offer in the current period, but this effect is relatively small. The proposers’ beliefs about the minimum amount that responders will accept is significantly higher than the minimum amount responders believe will be accepted by other responders. The proposer’s belief about the minimal acceptable offer does not change following a rejection. Nevertheless, the proposer’s offer in the next period does increase following a rejection. The probability of rejection increases when the responder has higher expectations about the amount that will be offered to him or higher beliefs about the minimal amount that other responders will accept.